2014
DOI: 10.1080/03066150.2014.937709
|View full text |Cite
|
Sign up to set email alerts
|

Life in a shrimp zone: aqua- and other cultures of Bangladesh's coastal landscape

Abstract: Degrowth refers to a radical politico-economic reorganisation that leads to smaller and more equitable social metabolisms. Degrowth posits that such a transition is indispensable but also desirable. However, the conditions of its realisation require more research. This article argues that critical agrarian studies (CAS) and degrowth can enrich each other. The Agrarian Question and the Growth Question should be addressed in concert. While degrowth should not fall into the 'agrarian myth', CAS should not embrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 67 publications
3
66
0
Order By: Relevance
“…This 'blue revolution' was not unique to Bangladesh; export oriented aquaculture transitions were promoted in poor indebted countries by international financial institutions to foster economic growth and food sovereignty (Pokrant 2014;Nuruzzaman 2006). Commodification of peasant livelihoods brought about by these neoliberal policies resulted in new forms of capitalist accumulation and reshaped class relations in rural Bangladesh (Paprocki and Cons 2014). The social, political and environmental effects of such agrarian transitions have been well documented in the sociology and development literature, often dichotomising the society into poor and nonpoor or providing descriptive narratives at aggregate level (Belton 2016;Adnan 2013;Swapan and Gavin 2011;Islam 2008).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…This 'blue revolution' was not unique to Bangladesh; export oriented aquaculture transitions were promoted in poor indebted countries by international financial institutions to foster economic growth and food sovereignty (Pokrant 2014;Nuruzzaman 2006). Commodification of peasant livelihoods brought about by these neoliberal policies resulted in new forms of capitalist accumulation and reshaped class relations in rural Bangladesh (Paprocki and Cons 2014). The social, political and environmental effects of such agrarian transitions have been well documented in the sociology and development literature, often dichotomising the society into poor and nonpoor or providing descriptive narratives at aggregate level (Belton 2016;Adnan 2013;Swapan and Gavin 2011;Islam 2008).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…On the contrary, as the contribution by Paprocki and Cons indicates, this transformation can exacerbate other sorts of problems. Based on a carefully controlled study of two polders in Bangladesh -one subsistenceoriented and the other entirely given over to shrimp aquaculture -they argue that food sovereignty permits 'a full spectrum of agrarian classes to continue to be peasants, though it does not necessarily yield greater equality in agrarian class relations' (Paprocki andCons 2014, 1111). In particular, despite some food sovereignty advocates' claims to the contrary, they suggest that the implementation of food sovereignty per se does little to address problems of landlessness.…”
Section: Origins Of 'Food Sovereignty'mentioning
confidence: 99%
“…For example, politically influential shrimp farmers often expanded their shrimp ponds by systematically and wrongfully subjugating agricultural farmers to convert their agricultural lands. Paprocki and Cons (2014), as an illustration, reported that in polder 20 and 23, sluice gates were taken over and embankments were cut in places to inundate fertile lands, and thus poor agricultural farmers were evicted and their lands were usurped (see also Gain 1995, Ito 2002. Another example is the unemployment issue caused by CSF.…”
Section: Analysis Iii: Commercial Shrimp Farmingmentioning
confidence: 99%